The Evolving Impact of Advanced Nursing Roles on Health Outcomes, Quality, and Patient Experience: A Systematic Review - Alasmari, Azah Muadi; Mohd, Wejdan Ibrahim; ALharbi, Seham Mohammed; Mahnashi, Tahane Ahmed; Hayyan, Areej Ail Mohammed; Alajmi, Abtahal Mohamed; Alharthi, Waad fuhaid; Jabri, Rana Jaber Al (Journal of Posthumanism, 2024)
Advanced nursing roles have expanded significantly over the past decade, driven by healthcare system complexity, workforce shortages, and the global shift toward patient-centered care. This systematic review examines the evolving impact of advanced nursing roles—such as nurse practitioners (NPs), clinical nurse specialists (CNSs), nurse educators, nurse informaticists, and advanced practice nurses (APNs)—on patient outcomes, healthcare quality, and patient experience. Electronic databases including PubMed, CINAHL, Scopus, and Web of Science were systematically searched for studies published between 2016 and 2025. Thirty-eight studies met the inclusion criteria. Findings reveal that advanced nursing roles contribute to measurable improvements in clinical outcomes, including reduced mortality, enhanced chronic disease management, fewer emergency visits, and improved medication adherence. Additionally, advanced practice nurses significantly enhance quality indicators by reducing errors, supporting evidence-based practice, and leading quality improvement initiatives. Patient experience outcomes also demonstrated positive trends, particularly in communication quality, trust, and overall satisfaction. This review concludes that advanced nursing roles serve as a transformative force in healthcare systems, improving service delivery efficiency and outcomes. However, variations in scope of practice, regulatory barriers, and workforce shortages remain challenges requiring policy attention.